The Use of Antisense-Mediated Inhibition to Delineate The Role of Inflammatory Agents in The Pathophysiology of Spinal Cord Injury - Damien D. Pearse; Francisco C. Pereira; Katina Chatzipanteli; Francisco W. Dalton Dietrich; Mary Bartlett Bunge (The Scientific World Journal)
Injuries to the central nervous system (CNS) usually lead to a potent and acute inflammatory response[1]. During this period, glia and immune cells respond to chemical cues associated with the debris of lysed neurons, disrupted axons, and a broken blood-brain-barrier by releasing a battery of cytokines including tumor necrosis factor-α (TNF-α) and, interleukin-β (IL-1β) as well as reactive oxygen species such as nitric oxide (NO-)[2]. The secretion of these factors may be primarily responsible for secondary damage to surrounding uninjured tissue that potentiates the initial injury[3]. Antisense oligonucleotides (ASOs) are designed to hybridize to specific regions of specific mRNAs. Hybridization of the oligonucleotide to the mRNA then interferes with the normal processing of that mRNA at the ribosome or targets the RNA duplex for cleavage by the RNA digestive enzyme, ribonuclease H, resulting in greatly reduced expression of the coded protein. This effectively reduces the amount of corresponding translated protein product and experiments can be designed to examine the requirement of particular inflammatory agents in eliciting specific deleterious responses after injury, e.g., cell death.